Identification of cytochrome P450 gene family and functional analysis of HgCYP33E1 from Heterodera glycines - You, Jia; Chen, Jingsheng; Hu, Yanfeng; Wang, Siru; Wang, Jianli; Sun, Tao; Shen, Zhongbao (Frontiers in Plant Science, 2023)
The cytochrome P450 (CYP) genes of nematode play a crucial role in the metabolic detoxification of xenobiotics including pesticides. Heterodera glycines, also known as the soybean cyst nematode, is a sedentary endoparasite that infests plant roots, causing high annual economic losses in soybean production regions globally. In this study, we identified 36 CYP genes at a genome-wide level of the H. glycines isolate TN10 using all CYPs from Caenorhabditis elegans as queries. Subsequently, a full-length cDNA of HgCYP33E1 which was significantly up-regulated by the conventional nematicide abamectin was initially cloned from H. glycines. It presented significantly higher expressions in the second-stage juvenile (J2) compared to other parasitic stages of H. glycines. qRT-PCR analysis suggested that the expression of HgCYP33E1 was also xenobioticly induced by soybean root exudate and the metabolites of biocontrol agents. Using RNA interference (RNAi), we investigated the function of HgCYP33E1 in H. glycines parasitism and nematicide selectivity. Compared to the control and dsGFP-treated group, silencing of HgCYP33E1 did not affect the J2 behaviours and the early invasion ability, while it decreased the number of J4s in soybean roots after 18-d inoculation with the dsHgCYP33E1-treated nematodes. In addition, knockdown of HgCYP33E1 in H. glycines resulted in an increase in J2 mortality after 24-h incubation with abamectin compared to the GFP dsRNA-soaked and the control group. These findings revealed the potential role of HgCYP33E1 in the xenobiotic detoxification pathway of H. glycines. Moreover, our data also provided valuable gene information for studying the functions of the CYP family in H. glycines host adaption.